Damages to stent stabilized left ventricular pacemaker electrodes during simulated lead extraction - Romola Laczkó; Tibor Balázs; Eszter Bognár; János Ginsztler (Fracture and Structural Integrity)
During biventricular pacemaker implantation stents can be applied for coronary sinus lead stabilization to prevent lead dislocations. A lot of issues have been raised in connection with the use of the stent. In some cases the implanted left ventricular lead must be explanted. It is crucial to avoid any injury to the heart when the electrode is removed. Another very important question concerns the type of injuries the electrode may cause during the removal process. An extraction model has been prepared using a special curve and a polymer tube. After the pacemaker leads were extracted, various microscopic examinations were executed. The findings may to make such intervention methods more successful, helping to better stabilize the electrode and to keep injuries during interventions to a minimum.